Clinico-microbiological study of dermatophytosis in a tertiary-care hospital in North Karnataka - Tonita M Noronha; Raghavendra S Tophakhane; Shobha Nadiger (Wolters Kluwer Medknow Publications, 2016)
Context: The dermatophytoses constitute a group of superficial fungal infections of keratinized tissues, namely, the epidermis, hair, and nails. The distribution and frequency of dermatophytosis and their etiologic agents vary according to the geographic region studied, the socio-economic level of the population, the time of study, the climatic variations, the presence of domestic animals, and age. Aims: The present study was undertaken to assess the clinical profile of dermatophytic infections and to identify the causative fungal species in the various clinical presentations. Settings and Design: This was a hospital-based observational study. Materials and Methods: One hundred and fifty clinically suspected cases of dermatophytosis attending the outpatient department of a tertiary care hospital were included in the study. History was taken, general physical and cutaneous examination was done and details of skin lesions noted. Direct microscopy in 10% KOH (40% KOH for nail) and fungal culture on SDA with 0.05% chloramphenicol and 0.5% cycloheximide was done in every case. Statistical Analysis Used: Statistical analysis was done using SPSS 17.0 software. Chi-square test and contingency coefficient test were used as significant tests for analysis. Results: Out of 150 patients studied, majority belonged to the age group of 21-30 years (22.7%). Male-to-female ratio was 1.63:1. Tinea corporis (24.7%) was the most common clinical type observed. The overall positivity by culture was 40% and by direct microscopy was 59.3%. Trichophyton mentagrophytes was the predominant species isolated (48.3%). Conclusions: The present study reveals the changing trend in the prevalence of dermatophyte species in this part of Karnataka.